1996
DOI: 10.1038/ng0196-44
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease susceptibility and hypertension are under independent genetic control in the fawn-hooded rat

Abstract: Hypertension, diabetes and hyperlipidemia are risk factors for life-threatening complications such as end-stage renal disease, coronary artery disease and stroke. Why some patients develop complications is unclear, but only susceptibility genes may be involved. To test this notion, we studied crosses involving the fawn-hooded rat, an animal model of hypertension that develops chronic renal failure. Here, we report the localization of two genes, Rf-1 and Rf-2, responsible for about half of the genetic variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(190 citation statements)
references
References 40 publications
10
180
0
Order By: Relevance
“…Based on the histological features of the FGS/Kist kidney, we here detected two QTLs for GSI, Gsi1&2, on Chrs 8 and 10. These QTLs were not homologous to those of the above rat models [2,4,19]. Thus, the FGS/Kist mouse may play an important role as a new source of QTLs to further FGS study.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Based on the histological features of the FGS/Kist kidney, we here detected two QTLs for GSI, Gsi1&2, on Chrs 8 and 10. These QTLs were not homologous to those of the above rat models [2,4,19]. Thus, the FGS/Kist mouse may play an important role as a new source of QTLs to further FGS study.…”
Section: Discussionmentioning
confidence: 90%
“…As the phenotypic effects of one locus on different traits, e.g. proteinuria and renal sclerosis score, are reported in the fawn-hooded hypertensive rat [2], Ptnu1 and Gsi1 may be potentially the same locus with pleiotropic effects on proteinuria and glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Brown et al 56 has identified a gene that predisposes to hypertensive renal injury and has no apparent effect on blood pressure. It is possible that this gene or other genes are linked with the failure of the afferent arteriole to antoregulate and therefore lead to a high glomerular pressure and hyperfiltration.…”
Section: Other Factors That Influence Renal Diseasementioning
confidence: 99%